2021
DOI: 10.3389/fgene.2021.703210
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a PPP1R12A-Related Five-Gene Signature Associated With Metabolism to Predict the Prognosis of Patients With Prostate Cancer

Abstract: BackgroundProstate cancer (PCa) is the most common malignant male neoplasm in the American male population. Our prior studies have demonstrated that protein phosphatase 1 regulatory subunit 12A (PPP1R12A) could be an efficient prognostic factor in patients with PCa, promoting further investigation. The present study attempted to construct a gene signature based on PPP1R12A and metabolism-related genes to predict the prognosis of PCa patients.MethodsThe mRNA expression profiles of 499 tumor and 52 normal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Interestingly, studies have shown that signature based on MetaGenes are associated with PCa recurrence undergoing radical prostatectomy ( 59 ). Two other researches also revealed that the model established by MetaGenes can predict the prognosis of PCa, which is consistent with our study ( 60 , 61 ). In summary, we conducted an integrated analysis to develop a metabolism-based four-gene signature for predicting the OS and chemo-/immuno-therapy response of PCa patients.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, studies have shown that signature based on MetaGenes are associated with PCa recurrence undergoing radical prostatectomy ( 59 ). Two other researches also revealed that the model established by MetaGenes can predict the prognosis of PCa, which is consistent with our study ( 60 , 61 ). In summary, we conducted an integrated analysis to develop a metabolism-based four-gene signature for predicting the OS and chemo-/immuno-therapy response of PCa patients.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, PPP1CB, predominantly expressed in muscle, promotes muscle tissue growth through its involvement in muscle cell proliferation and differentiation [ 76 , 77 ]. PPP1R12A regulates muscle cell characteristics such as growth, cycle, adhesion, and migration, and has a pivotal role in the control of muscle contraction and relaxation [ 78 , 79 ]. These results propose that PPP1CB and PPP1R12A have instrumental roles during early locomotor system development in A. fangsiao larvae, regulating muscle growth and development from multiple perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Only three genes out of the 107 genes investigated were found to be under positive selection (Figure3). PPP1R12A, where we identified positive selection signals in the common chimpanzee, is a gene implicated in adhesion, cell migration, and cancer treatment prognosis in humans(Benvenuto et al, 2020; Hughes et al, 2020;Zou et al, 2021). It also seems to interact with OT to enable uterine contraction(Hudson and López Bernal, 2017;Lartey and López Bernal, 2009).…”
mentioning
confidence: 85%